Organophosphites: An Addition to the Arsenal of Organocatalysts. Issue 4 (8th January 2023) - Baral, Nilofar; Rani, Soniya; Saikia, Pinku; Maity, Pradip
Abstract: Organophosphites are nucleophilic in nature and can act as a good leaving group owing to the stability of the phosphite anion. This dual reactivity makes them good candidates for nucleophilic organocatalysis. However, phosphites were introduced only in 2004 as the umpolung catalyst for acylsilane substrates utilizing sequential Brook rearrangements. Very recently, phosphites have been reported to catalyze aza ‐rearrangements and radical reactions. In this review, we discuss the reactivity parameters to understand its lack of use, as well as the potential for catalysis. Abstract : The development of organophosphite catalysis is introduced in the context of nucleophilic organocatalysis. Its unique characteristics were compared with other known nucleophile catalysts to describe new and complimentary reactions. In this review, we evaluate the reactivity pattern to provide our views on challenges, advantages, and potential applications of phosphite catalyst.